Patency testing improves capsule retention rates but at what cost? A retrospective look at patency testing - O'Hara, Fintan; Walker, Caroline; McNamara, Deirdre (Frontiers in Medicine, 2023)
Capsule retention is one of the major complications of capsule endoscopy. The rates of which range from 2.1% to 8.2% depending on the indication. Over the last few years reported rates of retention have fallen due to better patient selection due to recognition of risk factors for capsule retention as well as the introduction of the patency capsule.The patency capsule is a dissolvable capsule with the same dimensions as the functional capsule. It breaks down in the GI tract after approximately 30 hours reducing the risk of symptomatic retention. Failure to pass this patency capsule out of the small bowel results in the patient being excluded from capsule endoscopy.We performed a retrospective analysis of the patency capsules performed in our unit over a 12-month period. 166 (14.7%) of 1127 patients referred for capsule endoscopy were deemed to require patency assessment (45.8% male, mean age 48years). Of those who passed patency assessment and went on to capsule endoscopy no capsule retention was seen.Indication for patency assessment was found to be appropriate in 87.0% (n=147) Overall the failure rate at patency assessment was 43.1%. The patency capsule remains an imperfect but useful tool in examining for functional patency of the GI tract prior to capsule endoscopy.